PEMBERDAYAAN KELOMPOK WANITA DALAM PRODUKSI OLAHAN COKLAT - Suprayatmi, Mira (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2015)
Seeing the potential of natural resources, human resources as well as the functional of cocoa that can be processed into chocolate. The upstream and downstream industries development is needed. The downstream industry needs policies to encourage the growth of SMEs processing cocoa production. One of the constraints of SMEs growth among the society is the lack of knowledge about chocolate including cocoa processing. Whereas processed cocoa products could actually be produced in a household scale. Therefore it is necessary for training and mentoring program to develop the chocolate business groups in the community. Through the science and technology program, a development program was conducted to two housewives group (PKK) consist of 10 people in RW 07 Kedung Badak, tanah Sareal Bogor. The training provided are production of processed chocolate, exclusive packaging, hampers/parcel packaging, entrepreneurial motivation, on line marketing, basic finance and administration. The achievement of targets and outcomes of the program reach almost 100 percent. The groups of women have started businesses with their own brand chocolate products, receiving orders, assist in the marketing of chocolate stores and souvenir shops, held bazaars and fairs and even some members had participated as a training assistant of processed chocolate. Some constraints are the PKK group still has not registered PIRT and halal certificate with their own brands, they still cooperate with an SMEs partner. This is due to the waiting time on procedures for obtaining the certificate. Another obstacle is the problem of capital source for expansion, including semi-automatic packaging equipment.